Jati diri perempuan asli Fakfak / Ina V. Samosir Lefaan, Heppy Leunard Lelapary; editor Riris K. Toha-Sarumpaet, Avelinus Lefaan - SAMOSIR LEFAAN, Ina V; Heppy Leunard Lelapary; Sarumpaet, Riris K. Toha; Avelinus Lefaan (Pustaka Pelajar, 2016)
xxv, 156 hlm. : ilus. ; 23 cm.